Examination of Adolescents' Media and Technology Usages based on Various Demographics - Turel, Yalin Kilic; Dokumaci, Ozlem (Bucharest University Press, 2018)
Nowadays, due to rapid development of technology, users can easily access and purchase various information and communication technologies (ICT) with fair prices. Because of these changes our life habits are being changed day by day. In order to examine how Adolescents-as the future consumers- will be affected by these changes it is necessary to focus on their actual use of media and technology. While we were working on the adolescents' daily activities such as watching TV and movies, listening to music, playing video games, and listening to radio before the time Internet was not as prevalent as today, now we have to focus on the frequencies and densities of the use of contemporary internet based technologies such as social media, digital collaborative games etc. Thus, while considering the pervasive use of smart phones, the purpose of this research study is to examine adolescents' use of media and technology in terms of several demographic variables including gender, grades, ownership of electronic devices (tablet, smart phone etc.), parents' educational levels and so forth. Based on this purpose, a questionnaire that consists of two forms -Personal Information Form and Media and Technology Usage and Attitude Survey- conducted over 1278 students from 7th ,8th , and 9th grades in two different cities in the middle eastern part of Turkiye. Consequently, we found that there was no meaningful difference of students' use of media and technology based on gender and educational level of mothers while there were meaningful differences based on students' grades and educational levels of their fathers. The findings is hoped to shed light for stakeholders and policymakers.
13th International Conference on Virtual Learning (ICVL 2018) -- OCT 26-27, 2018 -- December 1st 1918 Univ Alba Iulia, Alba Iulla, ROMANIA
Keywords: Media; technology; demographics; adolescents; smart phones